Assessing the impact of aquaculture on the Seven Lakes of San Pablo, Philippines, using palaeolimnology - Briddon, Charlotte (2021)
In the Philippines, aquaculture in freshwater lakes contributes significantly to its economy, food security and employment. However, intensive aquaculture often leads to degradation in lake ecosystem integrity because of nutrient fertilisation resulting in harmful algal blooms (HABs), eutrophication and degradation of water quality. The few limnological and palaeolimnological studies carried out on Philippine lakes demonstrate a link between aquaculture activity and degraded water quality but there is a lack of information to help define how lakes have reacted over time to changing intensities of aquaculture and other catchment effects. This research attempts to redress this imbalance by using two different palaeolimnological approaches to assess the impact of aquaculture on six of the Seven Lakes of San Pablo (Luzon Island). Both approaches used multiple proxies, specifically, chlorophyll and carotenoid pigments, carbon and nitrogen isotopes (δ13C, δ15N) and C/N ratios to help disentangle lake-specific effects of aquaculture from the impacts of regional drivers. The first approach used generalised additive models (GAMs) to assess responses of lakes along an aquaculture disturbance gradient and hence whether lake response was proportional to the level of aquaculture. The second approach endeavoured to quantify the extent to which aquaculture (and other drivers) led to change in algal communities using variance partitioning analysis. Using this whole-ecosystem “experimental design” across individual lakes allowed for a more critical interpretation of the pigment and isotopic records. Both approaches concluded that there was no proportional relationship between changes in the proxy record and level of aquaculture disturbance, suggesting aquaculture is not the main driver of change. Land use changes (since 1950) explained the greatest proportion of variance and corresponded to periods of significant temporal change indicating it was a more dominant driver of change in algal communities. As aquaculture intensity increased, lakes became more eutrophic and anoxia increased due to nutrient enrichment from a combination of anthropogenic (urbanisation, coconut plantations and aquaculture) and climatic factors. In the majority of the lakes, changes in the proxy records predate the introduction of aquaculture, providing evidence that aquaculture exacerbated pre-existing change especially in the lakes with the highest aquaculture disturbance. Furthermore, each lake had a distinctive response to aquaculture due to the impact of multiple stressors (climate, land use and aquaculture) especially on the high disturbance lakes, and the modification by individual lake characteristics such as hydro-morphology. Mitigation strategies, therefore, need to be specifically developed for each lake, with consideration given to their distinct morphological features and how this influences their complex response to aquaculture and other environmental pressures.